Pregnancy loss after amniocentesis and chorionic villus sampling: Cohort study - Likar Ivana Paljk; Jere Ksenija Slavec; Možina Teja; Verdenik Ivan; Tul Nataša (Sciendo, 2020)
Introduction: To estimate the procedure-related risks of pregnancy loss following chorionic villus sampling (CVS) and amniocentesis (AC) compared to pregnancies without procedure.